Analisis Pelaksanaan Akad Murabahah Pada Pembiayaan Mikro di Bank BRI Syariah Kcp Subang. - Fuji Latipurohmah; Moch. Cahyo Sucipto; Rina Nurhayati (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
This article discusses Analysis of the Implementation of the Murabahah Agreement on Micro Financing at BRI Syariah Subculture Bank BRI. Sharia Economics Study Program, STIES Syariah Indonesia Purwakarta, 1441 H / 2019 M. Micro financing is bank financing to individual customers or business entities engaged in the MSME sector to finance their business needs through working capital financing or investment financing. Murabaha contract is the provision of funds or bills which can be equaled for the sale and purchase of goods at the principal price plus a margin based on the agreement or agreement between the Bank and the customer which requires the customer to repay his debt / obligation. This study aims to find out how the implementation of murabaha contract on micro financing at Bank Syariah Syariah Kcp Subang. And to find out the analysis of the implementation of the murabaha contract on micro financing at the BRI Syariah Subcapital Bank BRI. This research is a type of descriptive qualitative research that examines the implementation of murabaha contracts on micro financing at BRI Syariah Subcapit Bank BRI. The research data consisted of primary and secondary data obtained through questionnaires, observations, interviews and documentation. The data obtained were then analyzed using descriptive analysis methods. The results of this study note that the implementation of the murabahah contract on micro financing is theoretically the murabahah contract conducted by BRI Syariah Subcapitary Bank in conducting micro financing it can be said to be sharia when making a wakalah agreement first before making the murabahah contract after the item in question has become the property of the bank . Then the Bank sells it to the customer plus profit margins to be paid by the customer in a certain period, in accordance with the initial agreement.